Extended Drug Release Characteristics of Biodegradable Poly(lactic-co-glycolic acid) Microspheres: Overview - Giao Thong, Ngo; Thi Ha Lien, Nghiem; Thi Hai Yen, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 2, 2025)
Due to biodegradation and extended drug release from weeks to months, poly(lactic- co -glycolic acid) (PLGA) microspheres are increasingly researched and developed to load different types of active pharmaceutical ingredients with various therapy goals. However, limits in knowledge of the drug release mechanism, release model, and influential factors impede the preparation of appropriate microspheres for patients’ treatment requirements. Therefore, this overview aims to provide a better insight into the extended drug release characteristics of PLGA microspheres (drug release mechanism and release model) as well as influential factors (PLGA types, particle size, and pore density of microspheres) to support the research and development of microspheres formulations.